2018
DOI: 10.1039/c8ra00510a
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly synthesis of graphene–chitosan composite hydrogel as efficient adsorbent for Congo red

Abstract: A simple approach was utilized to synthesize graphene/chitosan-based hydrogel using glutaraldehyde as crosslinking agent in room temperature. The composite aerogel was used for removal of cationic and anionic dyes from aqueous solution. It showed high adsorption capacity towards Congo red as an anionic dye. Adsorption experiments were performed based on various parameters, such as initial Congo red concentration, solution pH and contact time. The kinetics data were analyzed using four different models and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(15 citation statements)
references
References 56 publications
2
13
0
Order By: Relevance
“…Finally, the X-ray diffraction pattern of the non-reticulated CS beads ( Figure 9 ) presented three peaks at 2θ values of 10°, 20°, and 41°, revealing the existence of amorphous regions and high crystallinity. This result is consistent with previous studies reported in the literature [ 23 , 48 , 49 , 50 , 51 ].…”
Section: Resultssupporting
confidence: 94%
“…Finally, the X-ray diffraction pattern of the non-reticulated CS beads ( Figure 9 ) presented three peaks at 2θ values of 10°, 20°, and 41°, revealing the existence of amorphous regions and high crystallinity. This result is consistent with previous studies reported in the literature [ 23 , 48 , 49 , 50 , 51 ].…”
Section: Resultssupporting
confidence: 94%
“…However, the acidic pH of dye solution gives rise to repulsion between adsorbent and adsorbate surface due to similar polarity over CR molecule and surface of PMC. On further increasing the pH above 7.0, excessive OH ions compete with the sulfonate groups of CR and the active site for dye adsorption is reduced compared to neutral pH which decreases the overall adsorption of CR dye onto PMC based adsorbent material 49 . Therefore, the prepared PMC based adsorbent materials effectively remove both contaminants (Cr(VI) and CR-dye) from water.…”
Section: Resultsmentioning
confidence: 99%
“…and the line with the lower slope (stage (II)) was attributed to the lower adsorption rate and intra-particle diffusion was the rate limiting step [65,66].…”
Section: Kinetics Adsorption Studiesmentioning
confidence: 99%